Influence of seismicity on the Lusi mud eruption. Issue 18 (22nd September 2015) - Rudolph, Maxwell L.; Manga, Michael; Tingay, Mark; Davies, Richard J.
Abstract Earthquakes trigger the eruption of mud and magmatic volcanoes and influence ongoing eruptive activity. One mechanism that could trigger an eruption is clay liquefaction. Here we model the propagation of seismic waves beneath the Lusi mud eruption (East Java, Indonesia) using available seismic velocity and density models to assess the effect of subsurface structure on the amplification of incident seismic waves. We find that using an updated subsurface density and velocity structure, there is no significant amplification of incident seismic energy in the Upper Kalibeng Formation, the source of the erupting solids. Hence, the hypothesis that the Lusi eruption was triggered by clay liquefaction appears unlikely to be correct. Independent constraints from gas chemistry as well as analyses of drilling activities at the nearby Banjar‐Panji 1 gas exploration well and an analysis of the effects of other earthquakes all favor a drilling trigger.